New species of Curculionichthys (Siluriformes: Loricariidae) from the eastern Guiana Shield - Silva, Gabriel S. C. [UNESP]; Roxo, Fabio F. [UNESP]; Melo, Bruno F. [UNESP]; Oliveira, Claudio [UNESP] (Magnolia Press, 2016)
We describe a new species of Curculionichthys from northern Brazil. The new species is known from the rio Cassiporee, an Atlantic coastal river and an unnamed affluent of the rio Jari, left tributary of the Amazon river. It can be distinguished from congeners by (1) the irregular concentration of chromatophores that cover the anal-fin origin and adjacent region, and distal portions of the first unbranched anal-fin ray, (2) lack of dark-brown spots scattered over the body, (3) lack of contrasting dark spots over the anterodorsal region of the body, (4) presence of papillae randomly distributed across the lower lip, (5) small, inconspicuous odontodes that form rows over the head and trunk, (6) anterior profile of the head pointed, (7) higher number of premaxillary and dentary teeth, (8) lack of an unpaired platelet on the dorsal portion of the caudal peduncle, (9) lower number of vertebrae, and (10) higher number of lateral abdomen plates. A discussion on the morphological variation of diagnostic features within Curculionichthys is also provided.
Keywords: Amazon basin; Cascudinhos; Freshwater fishes; Otothyrini; taxonomy